The Lady with Many Faces: The identity of the “Woman” in Apocalypse 12 - CHIANG, Yao-Kuo Eric (Journal of Research for Christianity in China (JRCC), 2025)
In the Book of Revelation, who is the “woman” in Chapter 12? The author John did not provide an answer in this chapter or the Book of Revelation, so her identity remains a mystery! According to the research of Bertrand Buby, there have been 28 interpretations of “woman”, and the woman is like a “lady with many faces”. This article sorts out four main types of the woman's identity - Type 1 “Mary”, Type 2 “Church”, Type 3 “Israel”, and Type 4 “People of God”. The author uses two hermeneutical rules to examine the rationality of the four main types.
Keywords: Apocalypse, Revelation, woman, typology